2021
DOI: 10.1039/d1cp01082d
|View full text |Cite
|
Sign up to set email alerts
|

Tin deposition on ruthenium and its influence on blistering in multi-layer mirrors

Abstract: A monolayer of Sn makes the Ru surface more permeable to H, but more layers inhibit H penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…The surface hydroxyl groups are referred to as reaction sites for the reaction illustrated in Figure B, so TDMASn forms a single monolayer on the S-1 support. The previous literature showed that the growth of SnO 2 was Stranski–Krastanov . It could be seen from the TEM that the particle size of Pt/20SnO 2 /S-1 (3.7 nm) was larger than that of Pt/20TDMASn/S-1 (2.7 nm).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The surface hydroxyl groups are referred to as reaction sites for the reaction illustrated in Figure B, so TDMASn forms a single monolayer on the S-1 support. The previous literature showed that the growth of SnO 2 was Stranski–Krastanov . It could be seen from the TEM that the particle size of Pt/20SnO 2 /S-1 (3.7 nm) was larger than that of Pt/20TDMASn/S-1 (2.7 nm).…”
Section: Discussionmentioning
confidence: 82%
“…The previous literature showed that the growth of SnO 2 was Stranski−Krastanov. 45 It could be seen from the TEM that the particle size of Pt/20SnO 2 /S-1 (3.7 nm) was larger than that of Pt/20TDMASn/S-1 (2.7 nm). This result corresponded to weaker interactions between the metal species and the support of Pt/20SnO 2 /S-1, which was in good agreement with the H 2 -TPR results.…”
Section: Discussionmentioning
confidence: 89%
“…However, the removal force for Sn from TaN remains low irrespective of the aging period and treatment temperature. On the other hand, Pb particles on TaN exhibits high removal force indicating that the Pb adheres to TaN strongly but not as high as Sn on The strong interaction of Sn on Ru surfaces as reported in the literature makes the removal of Sn contaminants difficult from the Ru substrate [16].…”
Section: Quantitative Analysis Of Removal Force For Pb and Sn Contami...mentioning
confidence: 84%
“…The acceleration of the deuterium uptake induced by Sn, as shown in Figure 6, is qualitatively consistent with the predictions based on DFT in. 10,11 According to these studies, when a Sn atom or a Sn hydride molecule is adsorbed on the Ru(0001) surface, charge transfer from Sn to H and Ru reduces their atomic volumes, making hydrogen penetration more favorable. This also holds for a complete atomic layer of Sn on Ru because hydrogen can access the Ru lattice through the Sn layer, given the larger atom size of Sn than Ru.…”
Section: Less Than One Atomic Layer Ofmentioning
confidence: 99%